Pyrolyzed cobalt hexacyanocobaltate dispersed on reduced-graphene-oxide as an electrocatalyst of the oxygen reduction reaction in an alkaline medium. Issue 13 (17th March 2023) - Zakrzewska, B.; Jabłońska, A.; Adamczyk, L.; Dembińska, B.; Kostuch, A.; Strawski, M.; Rutkowska, I. A.; Kulesza, P. J.; Marcinek, M.; Cox, J. A.; Miecznikowski, K.
Abstract : This article details the development of noble-metal free electrocatalytic materials based on Prussian blue analogue (metal–organic-type framework) immobilized on reduced graphene oxide for oxygen reduction reaction in alkaline medium. Abstract : Described is the development of a unique electrocatalytic material prepared by heat-treating a composite of a Prussian blue analogue, cobalt hexacyanocobaltate, and immobilizing it on reduced graphene oxide (rGO). The pyrolysis process, heating at 500 °C, forms a material with catalytic cobalt centers that are active toward the electrochemical oxygen reduction reaction in alkaline media. Physicochemical properties of this material containing cobalt in different oxidation states have been elucidated using transmission electron microscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, and various electrochemical diagnostic techniques. Experimental results have shown that this material displayed comparable electrocatalytic activity ( e.g., onset potential) toward the oxygen reduction reaction in alkaline media to that of Vulcan-supported platinum nanoparticles. Formation of undesirable peroxide species, as demonstrated by monitoring ring currents during rotating ring-disk electrode measurements, was somewhat higher at the pyrolyzed cobalt hexacyanocobaltate on rGO than with platinum nanoparticles on a carbon black support; however, even in the worst case, these values were below 15%, which demonstrates a high activity of cyanide-bridged cobalt sites. This thermally prepared electrocatalytic material exhibits high stability and tolerance to alcohols such as methanol.